935. VACHELLIA ANEGADENSIS. (16th May 2020) - Bárrios, Sara; Hamilton, Martin; Corcoran, Marcella; Woodfield‐Pascoe, Nancy; Clubbe, Colin
Summary: Vachellia anegadensis (Britton) Seigler & Ebinger, a spiny tree endemic to the British Virgin Islands (BVI), a Caribbean UK Overseas Territory, is described and illustrated. It is one of the four known endemic plant species to occur in the BVI, an archipelago of only 153 km 2 . It has been assessed as Endangered (EN) based on the IUCN categories and criteria. Its botanical history and conservation status are described, and ex situ propagation discussed.